Implikasi Motivasi dan Kompensasi dalam Membangun Kemandirian melalui Kegiatan Entrepreneur pada Lembaga Sosial Yatim dan Duafa - Rosida, Ika Nazilatur (Program Studi Ekonomi Syariah STAI Senori Tuban, 2024)
The spirit of independence and not begging is something that needs to be instilled in orphans and the poor. This research uses a qualitative case study method. This research aims to describe the implications of motivation and compensation in building independence through entrepreneurial activities that occur within the Al Madina Surabaya Foundation. This research is qualitative, case studies, and policy studies using field research methods. The data used in this research is primary data and secondary data. Data collection techniques using observation, interviews, and documentation. The validation technique used in this research is triangulation of primary data and secondary data. The research results show that providing motivation and compensation to orphans and the poor at the Al Madina Foundation can build their independence. Orphans and poor people carry out entrepreneurial activities in the form of buying and selling snacks. Buying and selling are done during school holidays and are sometimes brought to school and left in the canteen, so as not to disturb them in the education process. The proceeds from sales are given to orphans and the needy and capital comes from the foundation. Data collection in this research was by direct interviews, reading, and coming from online books, journals, scientific articles, and literature reviews containing the implications of motivation and compensation in building independence through entrepreneurial activities.